Faktor yang Mempengaruhi Kinerja Pegawai Dalam Pelaksanaan Tugas di Dinas Kesejahteraan Sosial Kabupaten Kutai Timur - Roby Roby (PREDIKSI : Jurnal Administrasi dan Kebijakan, 2020)
The purpose of this study is to find out the factors that affect employee performance in improving the implementation of tasks in the Social Welfare Office of East Kutai Regency. People with Social Welfare Problems (PMKS) is a person, family, or community group who due to an obstacle, difficulty, or disorder cannot carry out their social functions so that their needs are not met both physically, spiritually, and socially adequately and reasonably. While the Potential and Source of Social Welfare (PSKS) is the potential and resources that exist in humans, nature and social institutions that can be used for social welfare efforts. Autonomy and Assistance Duties in accordance with East Kutai Regency Regional Regulation No. 6 of 20013 in the field of Social Welfare, are: a). Formulation of policies in the field of Social Welfare; b). The implementation of government affairs and public services in the field of social welfare and community protection; c) The construction and implementation of social welfare and the protection of society; c) The implementation of other duties given by the Regent in accordance with its duties and functions. Some social problems in the main problems of the East Kutai Regency Social Service are a). Poverty problem; b) Low quality of human resources; c) Economic inequality around industrial estates; d) Decrease in the quality of the environment; Gap e). inter-regional and inter-regional development. The purpose of the medium-term work program of the East Kutai regency social service can be formulated as follows: a). The realization of quality social welfare human resources; b) The realization of good service with strategic collaboration; c). The realization of regional cooperation in the East Kalimantan region to realize East Kutai Regency as a free area on social welfare issues; d). The realization of coordination with vertical agencies for the optimization of funding sources; e). The realization of the improvement and equitable distribution of Social Services is fairer and more equitable.Tujuan dari penelitian ini adalah Untuk Mengetahui Faktor Yang Mempengaruhi Kinerja Pegawai Dalam Meningkatkan Pelaksanaan Tugas Di Dinas Kesejahteraan Sosial Kabupaten Kutai Timur. Penyandang Masalah Kesejahteraan Sosial (PMKS) adalah seseorang, keluarga atau kelompok masyarakat yang karena suatu hambatan, kesulitan, atau gangguan tidak dapat melaksanakan fungsi sosialnya sehingga tidak terpenuhi kebutuhan hidupnya baik jasmani, rohani, maupun sosial secara memadai dan wajar. Sedangkan Potensi dan Sumber Kesejahteraan Sosial (PSKS) adalah potensi dan sumber yang ada pada manusia, alam dan institusi sosial yang dapat digunakan untuk usaha kesejahteraan sosial. Otonomi dan Tugas Pembantuan sesuai dengan Peraturan Daerah Kabupaten Kutai Timur Nomor 6 Tahun 20013 di bidang Kesejahteraan Sosial, adalah : a). Perumusan kebijakan dalam bidang Kesejahteraan Sosial; b).Penyelenggaraan urusan pemerintah dan pelayanan umum di bidang kesejahteraan sosial dan perlindungan masyarakat; c). Pembinaan dan pelaksanaan kesejahteraan sosial dan perlindungan masyarakat; c). Pelaksanaan tugas lain yang diberikan oleh Bupati sesuai dengan tugas dan fungsinya. Beberapa masalah sosial dalam permasalahan pokok Dinas Sosial Kabupaten Kutai timur adalah : a). Masalah Kemiskinan ; b). Rendahnya kualitas sumber daya manusia ; c). Kesenjangan ekonomi di sekitar kawasan industri ; d). Penurunan kualitas lingkungan hidup ; Kesenjangan e). bangunan antar dan inter wilayah. Tujuan program kerja jangka menengah dinas sosial Kabupaten Kutai Timur dapat dirumuskan sebagai berikut : a). Terwujudnya sumber daya manusia bidang kesejahteraan sosial yang berkualitas; b). Terwujudnya pelayanan yang baik dengan kolaborasi yang strategis; c). Terwujudnya kerjasama regional di kawasan Kalimantan Timur dalam rangka mewujudkan Kabupaten Kutai Timur sebagai daerah yang bebas terhadap masalah-masalah kesejahteraan sosial; d). Terwujudnya koordinasi dengan instansi vertikal guna optimalisasi sumber pendanaan; e). Terwujudnya peningkatan dan pemerataan Pelayanan Sosial yang lebih adil dan merata.